Training of trainers’ guide on Improving child health and nutrition through diets, feeding and hygiene practices - Rahaman, E.H.M.S.; Chanda, D.; Hossain, M.; Ibrahim, Farhana Hussain (International Potato Center, 2023)
This is a guide on nutrition, child health and hygiene used for training of trainers in Community Nutrition Scholar Program in Bangladesh. The guide has following 11 components.